Simultaneous occurrence of follicular lymphoma and mixed-cellularity Hodgkin's lymphoma: lymph node and extranodal involvement - Maria do Patrocínio F. Grangeiro; Sílvia Maria M. Magalhães; Francisco Valdeci A. Ferreira; Francisco Dário Rocha Filho (Sociedade Brasileira de Patologia Clínica, 2004)
An unusual and well-characterised case of composite lymphoma in the spleen and lymph node is presented. The simultaneous occurrence of mixed-cellularity Hodgkin's lymphoma (HL) and follicular non-Hodgkin's lymphoma (NHL) was demonstrated in a 66-year-old man admitted in our Service with anaemia, hepatosplenomegaly and multiple abdominal lymph nodes. The morphological study of the spleen and lymph node of the splenic hilum showed an infiltrate composed of two distinct neoplasias. The liver was involved by NHL infiltrate and the peripancreatic lymph node exhibited HL. The Reed-Sternberg (RS) cells expressed CD 15 and CD 30, whereas the NHL cells presented standard immunohistochemical features of follicular lymphoma. To our knowledge, this is the fifth case report of concurrent spleen involvement by composite lymphoma. The incidence, clinicopathological and immunohistochemical features of this rare association are discussed.